The implementation of TQM in R&D. (1st January 1998) - Pearson, Alan W.; Vaughan, Nicci; Butler, Jeff
In 1992, a survey of over 40 UK companies was conducted to identify the progress being made in the implementation of quality management principles within R&D environments. Subsequently two workshops were organised to identify and explore areas of concern. The companies involved were selected because of their known interest in the subject. A variety of means were used to identify the "sample", including information from previous communications and studies by the R&D Research Unit, membership of TQM in R&D study groups, or mention in journals such as Total Quality Management. A telephone survey was conducted and thirteen companies were visited. Semi-structured interviews were conducted with R&D managers, quality managers and other employees. The companies visited were selected in order to illustrate a broad cross-section of experience in implementing quality management. The timing of their quality initiatives ranged from 1986 to embryonic stages in 1992. From the interviews and workshop discussions a model or framework was devised of the way in which TQM is implemented in R&D. This is presented in the paper with a recommendation that it be used to guide companies already in progress, or those companies still about to start.